Reversing the dominant directionality: Evidence of the East Asian model of gentrification in LA's Koreatown. Issue 2 (18th June 2019) - DeVerteuil, Geoff; Yun, Ohsoon
Abstract : Reversing the usual directionality of gentrification theory and process emanating from Anglo‐American models, we work from an East Asian model of gentrification via Seoul to see whether it has been emulated in the Global North, in this case Koreatown, Los Angeles. Focusing on the style, density, scale, scope and pace of the East Asian model and using interviews with 25 Korean gentrifiers and 10 key informants alongside secondary data, the results showed a mix of explicit emulation (density, new‐build) and no emulation at all (slow pace, small‐scale, punctuated scope), yielding a distinctly hybrid, Los Angeles‐style model that builds up a wider geography of gentrification. Abstract : Gentrification is usually seen to emanate from the Global North, but in this paper we attempt to see emulation from East Asia to the Global North, from Seoul to LA's Koreatown. The results point to an incomplete emulation, with a mix of higher density and high‐rise style alongside a slow, incremental gentrification.